An open & square stance case - Knudson, D. (coachesinfo.com)
Over a decade of experience with lighter, more power rackets has solidified the trend of greater use and acceptance of open stance forehand in tennis. What was once considered inferior technique, compared to the classic square stance forehand, is now commonly accepted a good tennis play. Unfortunately, some tennis and sport medicine experts have wondered if greater reliance on open stance forehand technique has contributed to the recent increase in overuse injuries of the back and arm. This paper will summarize the biomechanics of the open and square stance forehand, highlighting some of the recent research on this topic. The technique advantages and risks of injury are not an open and shut case, because these two styles are more similar than was previously thought. Professionals need to match the strengths and weakness of tennis techniques to the ability and goals of their clients.